Comparison of the snatch technique for female weightlifters at the 2008 Asian Championships - Ikeda, Y.; Jinji, T.; Matsubayashi, T.; Matsuo, A.; Inagaki, E.; Takemata, T.; Kikuta, M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to compare the snatch techniques of Japanese and international female weightlifters. Two high-speed cameras operating at 250 Hz were used to record the snatch lifts of the 5 best weightlifters in the snatch and 5 Japanese weightlifters during the 2008 Asian Weightlifting Championships held in Japan. The results revealed that the forward velocity of the barbell for the Japanese weightlifters during the second pull was significantly greater than that for the best weightlifters and that barbell trajectories of Japanese weightlifters except for the 53-kg class crossed the vertical reference line with great forward displacement of the barbell. In addition, the best weightlifters extended the knee and hip joints during the second pull earlier than the Japanese weightlifters did. These findings indicate that it is important to improve the way of pulling the barbell during the second pull for Japanese female weightlifters.